PENYULUHAN PENCEGAHAN STUNTING MENUJU KELUARGA BERKUALITAS - Suci, Stannia Cahaya; Zahara, Vadilla Mutia (UNIVERSITAS SERAMBI MEKKAH, 2024)
Stunting is a serious problem and also a major nutritional problem being faced in Indonesia. In 2023, the number of families at risk of stunting in Lebak Regency in 2023 will reach 13,780 people out of 58,801 people, so that 23.4% of the population are families at risk of stunting. The purpose of this service activity is to provide and increase understanding and knowledge about stunting prevention in pregnant women and children. The method used is the delivery of material and questions and answers. The impact of this service activity is to increase community knowledge based on pre-test and post-test results which show an increase in good category knowledge in the community by 80%.